2022
DOI: 10.3390/ijerph19138042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wuqinxi Qigong with Stretching on Single- and Dual-Task Gait, Motor Symptoms and Quality of Life in Parkinson’s Disease: A Preliminary Randomized Control Study

Abstract: The objective of this study was to investigate the therapeutic effect of Wuqinxi Qigong vs. stretching on single- and dual-task gait, motor symptoms, and quality of life in people with mild and moderate Parkinson’s disease (PD). This single-blind, randomized control trial included 40 participants with idiopathic PD who were randomized into the Wuqinxi Qigong (WQ) group or stretching group. Participants completed 12 weeks (two sessions/week) of intervention. The primary outcomes were gait parameters when perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…After selection, 58 studies ( Chaiwanichsiri et al, 2011 ; Duncan and Earhart, 2012 , 2014 ; Li et al, 2012 , 2018 , 2021 , 2022 ; Amano et al, 2013 ; Cheon et al, 2013 ; Corcos et al, 2013 ; Hye-Jung et al, 2013 ; Nocera et al, 2013 ; Volpe et al, 2013 ; Gao et al, 2014 ; Chen et al, 2015 ; Hashimoto et al, 2015 ; Rios Romenets et al, 2015 ; Sharma et al, 2015 ; Zhang et al, 2015 ; Choi, 2016 ; Kluger et al, 2016 ; Pantelyat et al, 2016 ; Ventura et al, 2016 ; Wong-Yu and Mak, 2016 ; Xiao and Zhuang, 2016 ; Kunkel et al, 2017 ; Lou et al, 2017 ; Cheung et al, 2018 ; Kong et al, 2018 ; Kurt et al, 2018 ; Lee et al, 2018 ; Michels et al, 2018 ; Van Puymbroeck et al, 2018 ; Vergara-Diaz et al, 2018 ; Kalyani et al, 2019 , 2020 ; Kwok et al, 2019 , 2022 ; Poier et al, 2019 ; Rawson et al, 2019 ; Solla et al, 2019 ; Wroblewska et al, 2019 ; Burt et al, 2020 ; Cancela et al, 2020 ; Dos Santos Delabary et al, 2020 ; Elangovan et al, 2020 ; Jang et al, 2020 ; Khuzema et al, 2020 ; Moon et al, 2020 ; Pohl et al, 2020 ; Cherup et al, 2021 ; Fodor et al, 2021 ; Frisaldi et al, 2021 ; Shen et al, 2021 ; Brandin-de la Cruz et al, 2022 ; ...…”
Section: Resultsunclassified
See 1 more Smart Citation
“…After selection, 58 studies ( Chaiwanichsiri et al, 2011 ; Duncan and Earhart, 2012 , 2014 ; Li et al, 2012 , 2018 , 2021 , 2022 ; Amano et al, 2013 ; Cheon et al, 2013 ; Corcos et al, 2013 ; Hye-Jung et al, 2013 ; Nocera et al, 2013 ; Volpe et al, 2013 ; Gao et al, 2014 ; Chen et al, 2015 ; Hashimoto et al, 2015 ; Rios Romenets et al, 2015 ; Sharma et al, 2015 ; Zhang et al, 2015 ; Choi, 2016 ; Kluger et al, 2016 ; Pantelyat et al, 2016 ; Ventura et al, 2016 ; Wong-Yu and Mak, 2016 ; Xiao and Zhuang, 2016 ; Kunkel et al, 2017 ; Lou et al, 2017 ; Cheung et al, 2018 ; Kong et al, 2018 ; Kurt et al, 2018 ; Lee et al, 2018 ; Michels et al, 2018 ; Van Puymbroeck et al, 2018 ; Vergara-Diaz et al, 2018 ; Kalyani et al, 2019 , 2020 ; Kwok et al, 2019 , 2022 ; Poier et al, 2019 ; Rawson et al, 2019 ; Solla et al, 2019 ; Wroblewska et al, 2019 ; Burt et al, 2020 ; Cancela et al, 2020 ; Dos Santos Delabary et al, 2020 ; Elangovan et al, 2020 ; Jang et al, 2020 ; Khuzema et al, 2020 ; Moon et al, 2020 ; Pohl et al, 2020 ; Cherup et al, 2021 ; Fodor et al, 2021 ; Frisaldi et al, 2021 ; Shen et al, 2021 ; Brandin-de la Cruz et al, 2022 ; ...…”
Section: Resultsunclassified
“…After selection, 58 studies (Chaiwanichsiri et al, 2011; Earhart, 2012, 2014;Li et al, 2012Li et al, , 2018Li et al, , 2021Li et al, , 2022Amano et al, 2013;Cheon et al, 2013;Corcos et al, 2013;Hye-Jung et al, 2013;Nocera et al, 2013;Volpe et al, 2013;Gao et al, 2014;Chen et al, 2015;Hashimoto et al, 2015;Rios Romenets et al, 2015;Sharma et al, 2015;Zhang et al, 2015;Choi, 2016; Kluger et al, 2016;Pantelyat et al, 2016;Ventura et al, 2016;Wong-Yu and Mak, 2016;Xiao and Zhuang, 2016;Kunkel et al,…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Thirteen studies reported the data from UPDRS-III, including 16 outcomes 24 , 27 29 , 31 , 33 , 36 42 . We extracted nine data for eight studies on 6MWT 24 , 28 , 31 33 , 35 , 39 , 42 , but only six and four trials reported data on gait 24 , 25 , 31 , 34 , 36 , 43 and PDQ-39 33 , 37 , 39 , 42 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 33 , 37 , 39 , 42 provided data for PDQ-39. It was found that aerobic exercise had no significant associations with PDQ-39 in people with PD [SMD, −0.13 (95% CI, −0.39 to 0.13), p = 0.32, I 2 = 0%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the obtained model seem to be in accord with studies showing mean (median) values of both measures: (1) 0.88 m/s gait speed corresponded with 12.3 s in the study of Viccaro et [47]; (4) 0.8 m/s gait speed corresponded with 12.6 s in the TUG test with a gait speed of 1 m/s with TUG of 9.9 s. in 163 older subjects [48]; (5) 0.78 m/s gait speed corresponded with 14.1 s of TUG and 1.1 m/s gait speed corresponded with 9.7 s of TUG in older Chinese adults [34]; (6) 0.52 m/s gait speed corresponded with 28 s of TUG and 0.66 m/s gait speed corresponded with 20 s of TUG in patients with Alzheimer's disease [32]; (7) 0.8 m/s gait speed corresponded with 11.2 s in the TUG test while gait speed of 0.97 m/s with TUG of 10.1 s in patients with Parkinson's disease [49]; (8) 1.4 m/s gait speed corresponded with TUG of 5.3 s in Japanese community-dwelling older adults [50]. Therefore, the proposed model may be useful for calculations of gait speed or TUG in future studies, especially in meta-analyses.…”
Section: Discussionmentioning
confidence: 96%